Development Of HSPX Vaccine Against Latent Tuberculosis Using Adjuvant-Dependent T-Helper Alternating Peptide Strategy - Lew, Min Han (2020)
Cellular immunity is a critical factor to be considered in developing an effective vaccine against Mycobacterium tuberculosis. Crosstalk between CD4+ and CD8+ T-lymphocytes play central roles in initiating cytotoxic killing to the infected cells, contributing to a complete clearance of intracellular tuberculosis bacilli Mycobacterium tuberculosis during infection. Based on these principles, our study proposed a novel alternating MHC-restricted peptide vaccination strategy to improve the rise of antigen-specific CD8+ T-cell response against alpha-crystalline heat-shock protein (HspX). Combined adjuvant for synergistic stimulation of cellular immunity (CASAC) adjuvant was included in the vaccine regimen to improve their immunogenicity against HspX antigen. Results indicated that recombinant HspX protein was proven to be immunogenic in C57BL/6 mice, showing an improved antigen-specific IgG1 and IgG2a antibody secretion and memory CD8+ T-cell immunity under stimulation of CASAC adjuvant.